PENGARUH PENAMB AHAN SODIUM TRIPOLIFOSFAT (STPP) TERHADAP KARAKTERISTIK PATI SENTE (Alocasia macrorrhiza (L.) Schoot) YANG DIMODIFIKASI DENGAN METODE CROSS-LINKING - Novitasari, Silvia; Rai Widarta, I Wayan; Sri Wiadnyani, AA Istri (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2017)
Sente ( Alocasia macrorrhiza (L.) Schoot) is one of minor tuber. Sente containing a lot of nutrition such us carbohydrates 23,16%, so sente is can be used as alternative food. The research aimed to find effect substitution sodium tripoliphosphate (STPP) to the characteristic of modified sente starch and to determine the optimal concentration of STPP, to produce the best characteristic of modified sente starch. This study used experimental design by Completely Randomized Design (CRD). The experiment consisted of six levels concentrations: 0%, 1%, 3%, 5%, 7% and 9%. The whole treatment was replicated three time to obtain 18 unit experiment. Data was analyzed by analysis of variance and the treatment show effect is observed by Duncan Multiple Range Test (DMRT) . The results showed that consentration STPP influences of characteristic sente starch. The best characteristic modified sente starch was produced by 9% STPP concentration with phosphate content 0,33%, degree of substitution 0,0172, amylose content 16,13%, starch content 72,60%, swelling power 11,61 g/g, solubility 5,73%, gelatinization temperature at 85,1 o C and final viscosity 1130 Cp. The amilography profile results showed that STPP can change the properties of native starch paste gelatization of type B into type C, the modified starch having a high stability on the heating process.
Keywords: Cross-lingk ing, sente, starch, STPP